"Natura y ratio" en la especulación sobre el cosmos: Guillermo de Auxerre y Felipe el Canciller - Corso, Laura Estela (2008)
The present study examines the Platonic, Stoic and Ciceronian antecedents in the expositions of William of Auxerre and Philip the Chancellor in their respective Summae, both of which make “ius naturale” to be the guiding principle of the practical-moral life, and which thus provides ontological and anthropological foundations. In addition, the author also investigates the meanings of the term “natura” in the Roman legal tradition, as it persisted at the beginnings of the 13th century; finally, she also considers its philosophical basis.